2016
DOI: 10.1007/s00784-016-2021-y
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride/vitamin D tablet supplementation in infants—effects on dental health after 10 years

Abstract: Fluoride/vitamin D supplementation can be used in children for preventing caries in the primary dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
1
22
1
1
Order By: Relevance
“…Vitamin D treatment in children or in mothers during pregnancy were associated to caries incidence or experience in five papers [60,61,[64][65][66]. Two cross-sectional studies [67,71] were done associating vitamin C intake and caries (levels and experience) and erosion in children.…”
Section: Hard Dental Pathological Processesmentioning
confidence: 99%
“…Vitamin D treatment in children or in mothers during pregnancy were associated to caries incidence or experience in five papers [60,61,[64][65][66]. Two cross-sectional studies [67,71] were done associating vitamin C intake and caries (levels and experience) and erosion in children.…”
Section: Hard Dental Pathological Processesmentioning
confidence: 99%
“…A systematic review was made in the recent times regarding controlled clinical trials holding the data of 2827 kids. They analyzed the impact of Vitamin D supplementation in terms of prevention process of dental caries examined [50], [51]. The outputs of this research prove that the supplementation of Vitamin D alleviated the caries' risk in nearly 47% but the predictability is low as stated by Hujoel [50].…”
Section: Vitamin D Deficiency In Tooth Mineralization and Cariesmentioning
confidence: 94%
“…Several studies examined whether vitamin D deficiency was associated with MIH, HSPM, and dental caries [ 49 , 50 ]. Kühnisch et al suggested that increases in serum 25-hydroxyvitamin D concentrations were correlated with less MIH and dental caries in a 10-year-old group of children [ 51 ].…”
Section: Studies Of Mih In Japanmentioning
confidence: 99%